Original paperPrevalence of vitamin D receptor gene Fok I polymorphism in patients with systemic lupus erythematosus – a preliminary report - Bogaczewicz, Jarosław; Sysa-Jędrzejowska, Anna; Łukaszkiewicz, Jacek; Kaleta, Beata; Woźniacka, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction : Recognition of the allele responsible for the phenotype of osseous tissue in patients with systemic lupus erythematosus (SLE) would be an important step forward in diagnostic and preventive management in osteoporosis. Aim: To assess the frequency of the nuclear receptor of vitamin D (VDR) gene polymorphism Fok I in SLE patients in comparison to the control group. Material and methods : The study included 56 patients with SLE. The control group comprised 65 samples of blood samples received from healthy blood donors. DNA isolation was performed using Boom's technology on silicone magnetic particles in NucliSens® miniMAG™, followed by real-time polymerase chain reaction with the Simple Probe for Fok I . Results : In SLE patients, the distribution of ff homozygotes was 14.29% patients; that of the Ff heterozygotes was 60.71%, and of the FF homozygotes was 25%. In the control group, the distribution was 15.38% for ff homozygotes, 61.54% for Ff heterozygotes, and 23.08% for FF homozygotes. No significant difference in the frequency of Fok I between SLE patients and the control group was found. Conclusions : Our preliminary report indicates that the distribution of Fok I VDR gene polymorphism in patients with SLE is not significantly different from that of the general population.